A T Cell Receptor Sequencing-Based Assay Identifies Cross-Reactive Recall CD8+ T Cell Clonotypes Against Autologous HIV-1 Epitope Variants - Chan, Hok Yee; Zhang, Jiajia; Garliss, Caroline C.; Kwaa, Abena K.; Blankson, Joel N.; Smith, Kellie N. (Frontiers in Immunology, 2020)
HIV-1 positive elite controllers or suppressors control viral replication without antiretroviral therapy, likely via CTL-mediated elimination of infected cells, and therefore represent a model of an HIV-1 functional cure. Efforts to cure HIV-1 accordingly rely on the existence or generation of antigen-specific cytotoxic T lymphocytes (CTL) to eradicate infected cells upon reversal of latency. Detecting and quantifying these HIV-1-specific CTL responses will be crucial for developing vaccine and T cell-based immunotherapies. A recently developed assay, called MANAFEST, uses T cell receptor (TCR) V sequencing of peptide-stimulated cultures followed by a bioinformatic pipeline to identify neoantigen-specific T cells in cancer patients. This assay is more sensitive than conventional immune assays and therefore has the possibility to identify HIV-1 antigenic targets that have not been previously explored for vaccine or T cell immunotherapeutic strategies. Here we show that a modified version of the MANAFEST assay, called ViraFEST, can identify memory CD8+ T cell responses against autologous HIV-1 Gag and Nef epitope variants in an elite suppressor. Nine TCR V clonotypes were identified and 6 of these were cross-reactive for autologous variants or known escape variants. Our findings are a proof of principle that the ViraFEST assay can be used to detect and monitor these responses for downstream use in immunotherapeutic treatment approaches.